On the energy distribution of interface states and their relaxation time profiles in Al/pentacene/p-GaAs heterojunction diode - Safak, Yasemin; Soylu, Murat; Yakuphanoğlu, Fahrettin; Altindal, Semsettin (Amer Inst Physics, 2012)
The energy density distribution profile of the interface states (N-ss) and their relaxation time (tau) of Al/pentacene/p-GaAs heterojunction diodes were obtained from the admittance spectroscopy method, which is included in capacitance/conductance-voltage measurements in the frequency range of 10 kHz-1 MHz at room temperature. The values of N-ss were also obtained from the forward bias current-voltage measurements by taking into account voltage-dependent barrier height, and the results were compared with those obtained using admittance method. The values of N-ss and tau obtained from admittance measurements range from 1.53 x 10(11) eV(-1) cm(-2) and 1.33 mu s in (0.596-E-v) eV to 1.90 x 10(11) eV(-1) cm(-2) and 8.18 mu s in (0.673-E-v) eV, respectively. In addition, the values of N-ss were obtained using Hill-Coleman method as a function of frequency. The values of N-ss obtained from these three methods are in the same order and in good agreement with one another. Low values of N-ss can be attributed to the interfacial pentacene layer between metal and semiconductor. This magnitude of N-ss is very suitable for the fabrication of electronic devices. The C values of these diodes decrease with increasing frequency both in inversion and depletion regions, but give a peak in the accumulation region due to the effect of series resistance. The increase in C, especially at low frequencies, results from the presence of interface states at GaAs/pentacene interface. (C) 2012 American Institute of Physics. [doi:10.1063/1.3681371]
Keywords: Capacitance-Frequency Characteristics; Electrical Characterization; Si-Sio2 Interface; C-V; Conductance